Contaminants of Emerging Concern: Occurrence, Analytical Techniques, and Removal with Electrochemical Advanced Oxidation Processes with Special Emphasis in Latin America - Salazar-Gonzalez, R; Vidal-Fuentes, J; Vidal-Fuentes, J (Elsevier Ltd, 2024)
The occurrence of contaminants of emerging concern (CECs) in environmental systems is gradually more studied worldwide. However, in Latin America, the presence of contaminants of emerging concern, together with their environmental and toxicological impacts, has recently been gaining wide interest in the scientific community. This paper presents a critical review about the source, fate, and occurrence of distinct emerging contaminants reported during the last two decades in various countries of Latin America. In recent years, Brazil, Chile, and Colombia are the main countries that have conducted research on the presence of these pollutants in biological and aquatic compartments. Data gathered indicated that pharmaceuticals, pesticides, and personal care products are the most assessed CECs in Latin America, being the most common compounds the followings: atrazine, acenaphthene, caffeine, carbamazepine, ciprofloxacin, diclofenac, diuron, estrone, losartan, sulfamethoxazole, and trimethoprim. Most common analytical methodologies for identifying these compounds were HPLC and GC coupled with mass spectrometry with the potential to characterize and quantify complex substances in the environment at low concentrations. Most CECs’ monitoring and detection were observed near to urban areas which confirm the out-of-date wastewater treatment plants and sanitization infrastructures limiting the removal of these pollutants. Therefore, the implementation of tertiary treatment should be required. In this tenor, this review also summarizes some studies of CECs removal using electrochemical advanced oxidation processes that showed satisfactory performance. Finally, challenges, recommendations, and future perspectives are discussed. © 2024 Elsevier Ltd